2013
DOI: 10.1002/mrm.24838
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo porcine model to measure pH dependence of chemical exchange saturation transfer effect of glycosaminoglycan in the intervertebral disc

Abstract: Purpose Studies have linked low pH and loss of glycosaminoglycan (GAG) in the intervertebral discs (IVDs) of patients with discogenic back pain. The purpose of the present study is to determine whether the chemical exchange saturation transfer (CEST) effect of GAG (gagCEST) is pH-dependent and whether it can be used to detect pH changes in IVD specimens. Iopromide, a FDA approved agent for CT/X-Ray, was also evaluated as a pH-sensitive CEST probe to explore the agents’ potential to measure IVD pH. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…The gagCEST effect is considered sensitive to changes in pH value, which has been established in an ex vivo porcine model. 28 CEST imaging using the contrast agent iopamidol is a recently developed MRI technique that enables in vivo pH determination using a ratiometric approach. 29,30 The present study is limited by the lack of pH assessment in order to avoid the application of contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…The gagCEST effect is considered sensitive to changes in pH value, which has been established in an ex vivo porcine model. 28 CEST imaging using the contrast agent iopamidol is a recently developed MRI technique that enables in vivo pH determination using a ratiometric approach. 29,30 The present study is limited by the lack of pH assessment in order to avoid the application of contrast agent.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with T2 mapping, T1ρ imaging possesses a better dynamic range and, hence, a better sensitivity to tissue hydration and PG content change during IVDD . Chemical exchange saturation transfer (CEST) imaging can detect GAG loss, and several studies have demonstrated the feasibility of CEST imaging of GAG content and pH changes during IVDD . The use of 23 Na MRI has also been explored for measuring the sodium concentration in intervertebral disc as an index for fixed charge density and GAG content in the ECM .…”
Section: Introductionmentioning
confidence: 99%
“…The GAG phantoms scan in our study is different from that reported by Melkus et al (17). First, their study was performed at 7.0T, which has a larger resonance frequency separation between ÀOH and water protons than 3.0T.…”
Section: Discussionmentioning
confidence: 74%
“…In fact, a roughly linear relationship between ÀOH CEST and GAG concentration was discovered on phantoms (24,25). The pH dependence of ÀOH CEST has also been shown at 7.0T by Melkus et al (17), yet no effort has been made to characterize such relationship at 3.0T.…”
Section: Cestmentioning
confidence: 97%